Evaluation of Food for Work Programme (August-October, 1979) - Planning Commission (Planning Commission, 1980)
It is the general experience in India that die benefits of most of the welfare schemes and development programmes had accrued to the better oil. sections of the society. This has happened despite the fact that eradication of poverty and unemployment has been one of the main goals of our developmental efforts since independence. The poor strata, particularly in the rural area, have remained deprived of its due share. Recognising these facts, the Government decided to give more emphasis on agriculture and rural development.
Programme Evaluation Organisation Planning Commission Government of India